Characterization of strength and damage of hard rock pillars using a synthetic rock mass method. (April 2015) - Zhang, Y.; Stead, D.; Elmo, D.
Abstract: In this research a 3D Synthetic Rock Mass (SRM) method is used to numerically characterize the strength and damage of hard rock pillars. The SRM is an integrated model incorporating a Discrete Fracture Network (DFN) within a Particle Flow Code 3D (PFC3D) particle assembly. Based on the numerical results of a joint-free pillar model, laterally fixed loading platens are suggested to simulate uniaxial compression tests on rock pillars. An internal-strain loading method is meanwhile used to ensure more realistic model behaviour. The peak strength, post-peak strain-softening gradient and deformation modulus of a series of jointed pillar models are then quantified, in order to investigate the effects of the inserted joint sets. The simulated peak strengths demonstrate a U-shape relationship when the joint sets are rotated; the peak strength also decreases with increasing joint size. A brittle post-peak behaviour is observed for pillar models with vertical joint sets of low persistence, the post-peak behaviour becoming more ductile when the joint sets are inclined and of higher persistence. A correlation is identified between the post-peak pillar behaviour and the simulated tensile cracking events, where a brittle post-peak corresponds to a high cracking rate. The effects of the joint sets on the pillar deformation modulus are observed to be similar to the effects on the pillar peak strength. Particular attention is given to the characterization of the crack initiation stress ( σ ci ) and crack damage stress ( σ cd ) thresholds of each pillar model, where the ratio of the crack initiation stress/peak strength is between 0.3 and 0.45, and the ratio of the crack damage stress/peak strength is between 0.75 and 0.98. The simulated cracks are compared between the jointed pillars and detailed cracking modes are plotted as 3D views and as 2D thin layers for selected pillar models.